2015
DOI: 10.1180/minmag.2015.079.5.15
|View full text |Cite
|
Sign up to set email alerts
|

New structural data reveal benleonardite to be a member of the pearceite-polybasite group

Abstract: 13The determination of the crystal structure of benleonardite (S.G. P 3 m1; R = 0. 0321

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…6; Table 4); all symmetry elements connected with the higher hexagonal symmetry were found to be non-vanished. Along with the use of the higher-order anharmonic Gram-Charlier tensors for the description of Debye-Waller factors of Ag atoms (this approach has been described elsewhere, see e.g., Evain et al, 2006;Bindi et al, 2013Bindi et al, , 2015a, the refinement of the structure model converged to very acceptable values: Robs = 0.0741, wRobs = 0.1746, Rall = 0.1029 and wRall = 0.1873 for 2804 (I > 3σ(I)) and 4339 reflections and 304 refined parameters, respectively; the remaining residuals in the difference Fourier maps are 3.49 and -1.07 e.Å -3 . We report the experimental details and crystal data in Table 4, and atomic positions in Table 5.…”
Section: X-ray Crystallography and Structure Refinementmentioning
confidence: 99%
See 2 more Smart Citations
“…6; Table 4); all symmetry elements connected with the higher hexagonal symmetry were found to be non-vanished. Along with the use of the higher-order anharmonic Gram-Charlier tensors for the description of Debye-Waller factors of Ag atoms (this approach has been described elsewhere, see e.g., Evain et al, 2006;Bindi et al, 2013Bindi et al, , 2015a, the refinement of the structure model converged to very acceptable values: Robs = 0.0741, wRobs = 0.1746, Rall = 0.1029 and wRall = 0.1873 for 2804 (I > 3σ(I)) and 4339 reflections and 304 refined parameters, respectively; the remaining residuals in the difference Fourier maps are 3.49 and -1.07 e.Å -3 . We report the experimental details and crystal data in Table 4, and atomic positions in Table 5.…”
Section: X-ray Crystallography and Structure Refinementmentioning
confidence: 99%
“…The question of unusually short bonds in the two linear (Ag,Cu)-S bonding schemes was usually presented as a result of Cu presence and Cu -Ag mixing in the central site of the metal polyhedron, e.g., by Bindi et al (2006Bindi et al ( , 2015a for pearceite and for cupropearceite from Tsumeb, respectively. The latter compound has 1.0 Cu in the site and the linear coordination of 2.151 Å Cu-S bonds.…”
Section: Details Of the Module Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bindi et al (2015c) showed that benleonardite, originally reported as Ag 8 (Sb, As)Te 2 S 3 by Stanley et al (1986), is actually another member of the polybasite series. The benleonardite structure consists, as described above, of a stacking arrangement of [Ag 6 (Sb, As) 2 S 6 Te] 2À A and [Ag 9 Cu(S, Te) 2 Te 2 ] 2+ B layer modules.…”
Section: Polybasite Isotypic Series and Related Benleonardite And Fetmentioning
confidence: 99%
“…These are Ag-bear ing sulphosalts of gen eral for mula [M 6 T 2 S 7 ] [Ag 9 CuS 4 ], where M=Ag, Cu and T = As, Sb (Bindi et al, 2007a(Bindi et al, , 2013(Bindi et al, , 2015a. Oc ca sion ally, S is re placed by Se and Te (Bindi et al, 2007a(Bindi et al, , 2015b. Cupropearceite likely forms by the re place ment of Ag by Cu (Bindi et al, 2007a(Bindi et al, , 2013(Bindi et al, , 2015a.…”
Section: Introductionmentioning
confidence: 99%